Factors Influencing Students' Learning Motivation in Senior High Schools in Karanganyar - Nurul Khoiriyah (Informatics Education Department, Faculty of Teacher Training and Education, Universitas Sebelas Maret, 2025)
Learning motivation is a crucial element in determining the success of the learning process. This study aims to identify the internal and external factors influencing students' motivation and analyze the contribution of teachers' interventions in creating a positive learning environment. The study was conducted at Senior High Schools in Karanganyar using a qualitative descriptive approach. Data were collected through participatory classroom observations and systematically analyzed to describe the relationship between students' motivation and the learning environment. The findings indicate that students' motivation is influenced by internal factors, such as awareness of aspirations and future goals, and external factors, including family support, peer influence, and the learning environment atmosphere. Moreover, teacher strategies such as project-based learning, positive feedback, and counseling guidance were proven effective in enhancing students' motivation. A supportive emotional and physical learning environment also significantly contributes to better student engagement. This study concludes that students' motivation plays a central role in shaping a positive learning environment. Thus, strengthening project-based learning strategies, teacher training in personal approaches, and improving communication between schools and families are recommended to support students' academic success.